Global longitudinal strain and outcome after endoscopic mitral valve repair. (6th June 2022) - Kotrc, Martin; Bartunek, Jozef; Benes, Jan; Beles, Monika; Vanderheyden, Marc; Casselman, Filip; Ondrus, Tomas; Mo, Yujing; Praet, Frank Van; Penicka, Martin
Abstract: Aims: Identification of heart failure (HF) patients with secondary mitral regurgitation (SMR) that benefit from mitral valve (MV) repair remains challenging. We have focused on the role of left ventricular global longitudinal strain (LV‐GLS) and reservoir left atrial longitudinal strain (LASr) for the prediction of long‐term survival and reverse remodelling in patients with SMR undergoing endoscopic MV repair. Methods and results: The study population consisted of 110 patients (age 67 ± 11 years, 66% men) with symptomatic SMR undergoing isolated MV repair using a minimally invasive surgical approach. Speckle tracking‐derived LV‐GLS and LASr were assessed in apical views using vendor‐independent software. Over a median of 7.7 years (IQRs 2.9–11.2), 64 patients (58%) died. Significant reverse LV (↓ LVESVI >10 mL/m 2 ), LA (↓ LAVI >10 mL/m 2 ) remodelling or both were observed in 43 (39%), 37 (34%) and 19 (17%) patients, respectively. LV‐GLS (HR 0.68, 95% CI 0.58–0.79, P < 0.001) and LASr (HR 0.93, 95% CI 0.88–0.97, P < 0.01) but not LV ejection fraction (LVEF) and LA volume index (LAVi) emerged as independent predictors of all‐cause mortality in Cox regression analysis. LV‐GLS was the only independent predictor of LV reverse remodelling (OR 1.24, 95% CI 1.05–1.43, P < 0.001) whereas LAVi and LASr were both independent predictors of LA reverse remodelling (both P < 0.05). In patients with atrial fibrillation at baseline, only LASr was an independent predictor ( P < 0.05) of LA reverse remodelling. Conclusions: In patients with SMR undergoing endoscopic MV repair, LV‐GLS and LASr are independently associated with long‐term survival and reverse remodelling and may be helpful in selecting SMR patients who may benefit from this procedure.